Feelings, Attitudes, and Knowledge in the Learning Method Using Chatgpt among Students in Higher Education Institutions - Siti Yuliandi Binti Ahmad; Noorsakinah Sardar Hussain; Farah Farzana Ulul’Azmi; Nursyafiqah Najwa Binti Ismadi; Nur Farihin Elyani Mohd Fauzi; Nurulain Razali (Jurnal Audiens, 2024)
This research examines the use of artificial intelligence (AI), which is ChatGPT, as a learning method. The aim of this study is to measure the level of feelings, attitudes and knowledge in learning using ChatGPT among higher education institution students. The theory that researchers use is the ABC Model by Eagle & Chaiken (1998), which measures affection, behaviour, and cognition of ChatGPT as a learning method. The research was conducted among the Edu Hub Pagoh population, which uses Kulliyyah Sustainable Tourism and Contemporary Language (KSTCL) students as their sample, consisting of 42 respondents, which include 34 females (81%) and 8 males (19%).The method of this study quantitative method, which is cluster sampling. The findings confirm that all three variables show a positive response toward using ChatGPT as one of the learning methods, and the mean of the variables, which are affection, behavioural and cognitive, is 2.958, 2.852, and 2.924, respectively, and overall, the results are moderate. The positive response towards using ChatGPT as a learning method suggests the potential for its wider application in educational settings. The moderate mean values indicate room for improvement and optimization of the AI tool for better learning outcomes. The study also highlights the importance of considering students’ feelings, attitudes, and knowledge when implementing AI tools in learning, which could guide future research and development in this area. Furthermore, the gender disparity in the sample (81% females and 19% males) might suggest a need for further research to understand if gender influences the response to AI learning methods. Overall, the study underscores the potential of AI, like ChatGPT, in transforming learning experiences in higher education institutions.